Tourism for Peace and Community Engagement: A Soft Power Approach to Conflict Resolution - Priyanka Sharma; Parikshat Singh Manhas; Ranjeet Singh; Faheem Ashraf (ASEAN Journal on Hospitality and Tourism, 2023)
The study analyses the soft power approach to conflict resolution using tourism and community involvement initiatives. This study investigates the impact of Peace through Tourism (PTT) and Community participation (CP) on Conflict resolution (CR) in Border destinations of Jammu and Kashmir (UT) in order to explore the possibilities of promoting just, peaceful, and inclusive societies, as articulated by Sustainable Development Goal 16 (SDG 16). Using community involvement and tourism as a means to greatly minimise conflict of all kinds as the main objective, about 340 residents of border towns were polled with questionnaires. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modelling (SEM) were employed to test and validate the study's assumptions about the relationships between variables. Current research findings suggest that peace through tourism plays a key role in resolving conflict at destinations and may play a supportive role in building peace on a global and local scale. The results also showed that community participation in tourism development has a big effect on resolving conflicts and that community participation lets locals enjoy the benefits of tourism activities and gives them the power to improve their skills through small business ventures. The paper gives suggestions for how different groups can help build peace through cooperative tourism projects and community interaction based on tourism.